Оперативний контроль якості овочів за електричними характеристиками - Мідик, І.-М. В.; Лиса, О. В.; Midyk, Ihor; Lysa, Olha (Видавництво Львівської політехніки, 2018)
У роботі досліджено електричні характеристики овочевих соків для контролю вмісту у них важких металів. Контроль показників якості овочевого соку щодо його забруднення важкими металами здійснено імітансним методом. Для цього створено експериментальну установку, до складу якої входить ємнісний перетворювач (кондуктометрична комірка, заповнена досліджуваною рідиною – овочевим соком з різними добавками), RLС-метр, блок опрацювання результатів та керування. Сукупність результатів дослідження вмісту домішок методом вивчення активної та реактивної складових електропровідності на різних частотах показує, що для виявлення вмісту йонів міді (цинку), що суттєво перевищують гранично допустимі концентрації, необхідно і достатньо проведення простих досліджень активної компоненти електропровідності. Чутливішими до частотних проявів виявились дослідження соків на частоті 1000 Гц. Для виявлення вмісту йонів важких металів, що перевищують гранично допустимі концентрації, необхідно використовувати реактивну компоненту електропровідності.

Vegetables’ pollution by mercury, copper, zinc and arsenic concerning the EU standards is not permitted, whereas in Ukraine it has to be within the limits of permissible concentrations. The urgent task is to develop an express method for controlling the concentrations of heavy metals in vegetable production. We have investigated the electrical characteristics of vegetable juices aiming the operative control of heavy metals concentrations in them. The studies were conducted with help of the immitance method. For this purpose, an experimental installation was created; it consists of the capacitive transducer (a conductivity cell filled with investigated fluid – vegetable juice with various additives), an RLC-meter, a unit for processing results and control (computer). RLC-meter in asynchronous mode sends a test signal of sinusoidal form to a capacitive transducer. In response to the test signal on the RLS-meter, the characteristics of the studied liquid are received. For the samples of carrot juice with different contamination of copper and sodium ions we can admit the smoothness of the change in the active component of electrical conductivity on the frequency of the test signal indicating the absence of frequencyexpressed effects and emphasizing its ionic nature. The reactive component changes inversely proportional correlating to the content of impurities. The main result of current study with help of electrical conductivity method (active and reactive components) at different frequencies can be reduced to the next. To detect the copper (zinc) at the concentration that essentially exceeds the permissible, is enough to fulfill rather simple studies of electrical conductivity active component.
Operative controlof quality of vegetables by electrical characteristics
Keywords: електропровідність; імітанс; кондуктометрична комірка; активна складова; реактивна складова; Electrical conductivity; Immittance; Conductometric cell; Active component; Reactive component